Production of an antimicrobial peptide derived from slaughterhouse by-product and its potential application on meat as preservative. (15th November 2016) - Przybylski, Rémi; Firdaous, Loubna; Châtaigné, Gabrielle; Dhulster, Pascal; Nedjar, Naïma
Highlights: The α137–141 enzymatic production from bovine cruor was studied. The α137–141 production was studied at high bovine cruor concentrations. The α137–141 was applied on meat as food preservative. The α137–141 inhibited microbial growths, particularly coliform bacteria. The α137–141 reduced lipid oxidation of meat about 60%. Abstract: Bovine cruor, a slaughterhouse by-product, contains mainly hemoglobin, broadly described as a rich source of antimicrobial peptides. In the current context of food safety, bioactive peptides could be of interest as preservatives in the distribution of food products. The aim of this work was to study the α137–141 fragment of hemoglobin (Thr-Ser-Lys-Tyr-Arg), a small (653 Da) and hydrophilic antimicrobial peptide. Its production was fast, with more 65% finally produced at 24 h already produced after 30 min of hydrolysis with pepsin. Moreover, increasing substrate concentration (from 1 to 8% (w/v)) resulted in a proportional augmentation of α137–141 production (to 807.95 ± 41.03 mg L −1 ). The α137–141 application on meat as preservative (0.5%, w/w) reduced the lipid oxidation about 60% to delay meat rancidity. The α137–141 peptide also inhibited the microbial growths under refrigeration during 14 days. These antimicrobial effects were close to those of the butylated hydroxytoluene (BHT).